Hold on tight - Gray, Shelley Shepard (Gray, Shelley Shepard. Bridgeport Social Club series, 2019)
"Get ready to fall in love with Shelley Shepard Gray's Bridgeport Social Club again, where a poker night is so much more than a game of cards and an extraordinary community of ordinary men and women come together to offer love, light, and hope to everyone they encounter." --Amazon.com.